2018
DOI: 10.1111/wrr.12647
|View full text |Cite
|
Sign up to set email alerts
|

Role of Schwann cells in cutaneous wound healing

Abstract: Dermal wound healing is the process of repairing and remodeling skin following injury. Delayed or aberrant cutaneous healing poses a challenge for the health care system. The lack of detailed understanding of cellular and molecular mechanisms involved in this process hampers the development of effective targeted treatments. In a recent study, Parfejevs et al.-using state-of-the-art technologies, including in vivo sophisticated Cre/loxP techniques in combination with a mouse model of excisional cutaneous woundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…The hematopoietic stem cells, which give rise to all blood and immune cells throughout life, reside in a specific complex niche in the bone marrow, that supports the homeostasis of these cells, composed by osteoblasts, osteocytes, osteoclasts, endothelial cells, adipocytes, smooth muscle cells, pericytes, fibroblasts, macrophages, megakaryocytes, lymphocytes, hematopoietic progenitors, neutrophils, peripheral innervations, and Schwann cells [18,85,64,8689,19,9,10,90,93]. Recent studies have revealed distinct contributions of several cellular components of the bone marrow to different functions of hematopoietic stem cells regulation.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…The hematopoietic stem cells, which give rise to all blood and immune cells throughout life, reside in a specific complex niche in the bone marrow, that supports the homeostasis of these cells, composed by osteoblasts, osteocytes, osteoclasts, endothelial cells, adipocytes, smooth muscle cells, pericytes, fibroblasts, macrophages, megakaryocytes, lymphocytes, hematopoietic progenitors, neutrophils, peripheral innervations, and Schwann cells [18,85,64,8689,19,9,10,90,93]. Recent studies have revealed distinct contributions of several cellular components of the bone marrow to different functions of hematopoietic stem cells regulation.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…Peripheral nerves, which are derived from the neural crest, are essential to progenitor function during development and homeostasis of the mouse incisors (Kaukua et al, 2014; Zhao et al, 2014). Schwann cells contribute to diverse neuronal progenitor populations (Espinosa-Medina et al, 2014; Uesaka et al, 2015), and peripheral glia maintain salient roles in promoting both neuronal and non-neuronal tissue repair (Parfejevs et al, 2018; Richardson et al, 1980; Silva et al, 2018). This behavior is linked to Schwann cell transcriptional reprogramming and paracrine signaling by local Schwann cells (Clements et al, 2017; Johnston et al, 2016; Parfejevs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells are associated with aspects of cutaneous homeostasis and are known to play a role in multiple diseases (see Table for details). We now have significant experimental evidence that activated SCs contribute to wound healing, [ ] neurofibromatosis, [ ] leprosy [ ] and melanoma growth and invasion. [ ] Taken together with the known functions of SCs, these studies have highlighted a previous unappreciated role of SCs in cutaneous biology and pathology.…”
Section: Role Of Scs In Human Skin Physiology and Clinical Dermatologymentioning
confidence: 99%
“…Schwann cells, the glial cells of the peripheral nervous system (PNS), have received special attention because of their ability to support the regeneration of injured axons. [ ] Yet, recent discoveries have revealed important roles for SCs in non‐neural biology: gut homeostasis, [ ] stem cell maintenance, [ ] immune modulation, [ ] cutaneous wound healing [ ] and cancer progression. [ ] Given their abundance and distribution under the dermal‐epidermal junction, the question has been raised regarding their role in cutaneous homeostasis and neoplastic and inflammatory dermatoses.…”
Section: Introductionmentioning
confidence: 99%